WSI European collective bargaining report 2023/2024: Real wages still need to catch up after crisis losses - Thilo Janssen; Malte Lübker (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2024)
Real wages in the European Union continued their decline in 2023-despite an acceleration in nominal wage growth and falling inflation rates. For the current year, there are tentative only signs of a slow recovery of the purchasing power of wages. A resumption of real wage growth would stabilize the functional distribution of income and Trends in negotiated wage rates in the eurozone, 2000- 2023 Change from prior year, in per cent Source: European Central Bank (Indicator of negotiated wage rates) and European Commission, AMECO Database (current as of 15 May 2024), authors' calculations. strengthen domestic demand. However, even under this benign scenario, the crisis is not over from workers' point of view: They have borne the brunt of the real income losses associated with the energy price shock resulting from the Russian invasion of Ukraine. The lingering reduction in real wage levels means that wage policy still needs to catch up to contribute to a fairer distribution of the buren between labour and capital. – – Auch im Jahr 2023 sind die Reallöhne in der Europäischen Union weiter gesunken - trotz anziehenden Wachstums der Nominallöhne und fallender Inflationsraten. Erst für das laufende Jahr zeichnet sich eine langsame Erholung ab. Dies stabilisiert die Einkommensverteilung zwischen Arbeit und Kapital und stärkt die Binnennachfrage. Aus Sicht Entwicklung der Tariflöhne in der Euro-Zone, 2000-2023 Veränderungen zum Vorjahr in Prozent Quelle: Europäische Zentralbank (Tariflöhne) und AMECO-Datenbank der Europäischen Kommission (Version: 15. Mai 2024), Berechnungen des WSI. der Beschäftigten ist damit die Krise nicht überwunden: Sie haben den Großteil der realen Einkommenseinbußen getragen, die mit dem Energiepreisschock infolge des russischen Überfalls auf die Ukraine verbunden waren. Aus der nachwirkenden Absenkung des Reallohnniveaus ergibt sich für die Lohnpolitik weiterhin Aufholbedarf, um zu einer gerechteren Lastenverteilung zwischen Arbeit und Kapital beizutragen.
Keywords: 330